KALA DALAM BAHASA MELAYU MANADO - Pattipeluhu, John A.; Kalangi, Leika Maria Victoria (Kajian Linguistik, 2017)
This research aims to understand and to describe the process and rules of thetenses form in Manado Malay language. This research is conducted in Manadowhich is almost all the civilians use Manado Malay language as their dailycommunication.This Research uses qualitative descriptive method and structural linguisticsmethod as an approaching to do this research.The data collecting was in terms ofrecording and interviewing with informan and analyzed by Miles and Hubermanmodel of data analysis such as data reduction, data display and data conclusion.The result shows that there are three forms of tenses in Manado Malay languages.Those are present, past and future. The present tense is form by a prefix ba- whichis bound to a verb; past tense is formed by a partikel so and followed by a verband; future tense is formed by partikel mo and followed by a verb.Keywords: tenses, process, Manado-Malay, language